Morbidity and Mortality pattern of neonatal intensive care unit in a Medical College Hospital from South India - Dr. Chandrakala R. Iyer; Dr. Vinod Kumar Gornale; Dr. Harsha PJ; Dr. Nagendra Katwe; Suhas Prasad. V; Keerthivardhan Y (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Neonatal outcome is a sensitive indicator of availability, utilization and effectiveness of obstetrics and neonatal health care in the community. Review of hospital based mortality and morbidity pattern is critical to improve the quality of health care delivery system in that hospital.Objectives: To study the morbidity and mortality pattern of neonates admitted to neonatal intensive care unit (NICU) of a rural medical college hospital.Material and methods: All the neonates admitted to NICU from July 2013 to June 2015 were retrospectively analysed for demographic profile, short term morbidity and outcome.Results: 1580 neonates were admitted in the study period. 59.5% were Males, 63% were inborn, 75% were term babies and 59.5% had normal birth weight. 89.8% were admitted in early neonatal period. Important causes for admission were sepsis (24%)), birth asphyxia (23.6%), prematurity and low birth weight care (18.5%), Respiratory problems (13.9%) and hyperbilirubinemia (10.3%). The outcome of the admitted babies showed 83% discharges, 3.7% deaths, 12.2% discharge against medical advice and 1.96% referred to another centre. The major causes of mortality were birth asphyxia including hypoxic ischemic encephalopathy (45%), sepsis (27.5%) and respiratory problems (27.5%). The survival of term as well as inborn babies was better than that of preterm and out born neonates respectively.Conclusion: Birth asphyxia, neonatal sepsis, prematurity and respiratory problems were major causes of both mortality and morbidity. There is need to strengthen services to address these problems more effectively.